Detection of Weak D (Du) Phenotype among Rh-D Negative Males and Females in Kumasi, Ghana (Journal of Science and Technology, 2016)
Weak Rh D phenotypes are very frequent in Africans. They are capable of causing alloimmunization in Rh D-negative individuals. Some weak Ds may elude routine typing using direct agglutination techniques. This study aimed at determining the prevalence of weak D phenotype among Rhnegatives, using indirect antiglobulin technique. A total of 400 donors between the ages of 16 and 35 years who were grouped by the blood bank were randomly sampled over a period of 2 months. Three hundred and sixty nine (92.25%) were typed as Rh D-positive and 31 (7.75%) RhD-negative. Two (6.45%) of the Rh D-negative donors were weak D positive while 29 (93.55%) were weak D negative. Among the males 25 (9.43%) were Rh D-negative and 240 (90.57%) RhD-positive. Two (8%) of the 25 males were weak D positive. Among the females, 6 (4.44%) were Rh D-negative and129 (95.56%) RhD- positive. This implies that, there are people in Kumasi with weak D phenotype which cannot be detected by the direct monoclonal anti-D agglutination. Consequently, indirect antiglobulin test may be indicated for such individuals typed Rh D-negative. This study has shown the need for a comprehensive policy on appropriate testing of donors and newborns, and management of Rh D-negative mothers in the Region. This should include weak D testing of all Rh Dnegative blood donors before transfusion in Rh D-negative patient.